THE EXISTENTIAL PRINCIPLE IN RUSSIAN LITERATURE (Web of Teachers: Inderscience Research, 2025)
The article is dedicated to the study of existential motifs that permeate the works of Russian literary tradition. Special attention is given to issues such as the meaning of life, freedom, loneliness, and responsibility to oneself, which are reflected in the works of key Russian writers such as F.M. Dostoevsky, L.N. Tolstoy, A.P. Chekhov, and others. Particular focus is placed on the influence of existentialist philosophical ideas on the formation of the authors' artistic worldview, as well as their interpretation of human existence in the context of social and spiritual crises. The paper emphasizes the uniqueness of Russian literature in addressing existential problems, making it a significant contribution to world culture.